Antidepressant chronotherapeutics in a group of drug free outpatients. (30th July 2016) - Dallaspezia, Sara; van Jaarsveld, Astrid
Abstract: The combination of Total Sleep Deprivation (TSD) and Light Therapy (LT) has been shown to prevent the early relapses characterizing response to TSD. Despite their proved efficacy, TSD and LT are still far from being considered standard therapy in the inpatient units and no study has assessed their efficacy and feasibility in outpatient settings. We studied 27 drug-free out-patients affected by Major Depression, divided in 7 groups according to the date of the wake night. Patients were administered one night of TSD and received LT during consecutive mornings following a predictive algorithm based on Morningness-Eveningness Questionnaire scores. Severity of depression was rated on Back Depression Inventory Scale (BDI) at baseline, one week and three months after the end of treatment. BDI scores significantly decreased during treatment with no difference between the seven consecutively treated groups of patients. Significant differences in BDI scores were confirmed between the baseline and both one week and three months after the end of treatment. TSD and LT caused a significant amelioration of depressive symptoms in an outpatient setting. Similar effects were observed in seven independent groups, suggesting that there is repeatability in findings. Chronotherapeutics confirmed their efficacy in the treatment of depression. Highlights: Sleep Deprivation and Light Therapy (TSD+LT) can be used in outpatient settings. The antidepressant response to TSD+LT rested even without any adjunctive treatment. Similar effects were observed in independent groups.